UTILITY OF SILVER NITRATE STAINING IN DETECTION OF SPIROCHETES FROM ORAL CAVITY OF PERIODONTALLY HEALTHY AND DISEASED INDIVIDUALS - VARSHA CHOUDHARY; PREETI INGALAGI; DR.CHETANA BOGAR; DR.SUNIL RAO; DR. KISHORE BHAT (International Journal of Pharma and Bio Sciences, 2012)
Oral spirochetes play a definitive role in the etiology of periodontitis. But their study is hampered due to difficulty in cultivating them and molecular methods are expensive. Hence the study explores the possibility of using staining as a screening procedure for the study of oral spirochetes. Experimental approach: The study included 100 patients with chronic periodontitis and 100 controls. Subgingival plaques were collected and silver nitrate staining was performed. The positive slides were screened for density of organisms and an attempt was also made to determine the relative size of spirochetes and their predominance.Findings: There was a significant difference in the positivity rate between the patients and controls. Higher number of patients had greater density of spirochetes. The presence of large spirochetes in controls was significantly higher.Conclusions: Silver nitrate staining is a useful screening method for detection of spirochetes. It can also be used to assess the cell size, density and post therapy evaluation.